Fundamentos y límites de una economía de la justicia - Martínez Cinca, Carlos Diego (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2003)

(untitled)
The Economic Analysis of Law should be considered the most important bridge between Law and Economics at the present time. We can find its foundations in 1960’s, mainly since the publication of two great economists’ works: Ronald Coase (University of Chicago) and Guido Calabresi (University of Yale). Furthermore, several works of Richard Posner (University of Chicago Law School) have contributed to its diffusion beyond the frontiers of the american universities. In this paper, we show the internal structure of the Economic Analysis of Law, based upon the neoclassical model in Economics, and the main critics adressed to it from Institutional Economics as well as from Legal Theory.